IN VITRO COMPARATIVE STUDY OF THE ANTIOXIDANT ACTIVITY OF METHANOLIC LEAF AND STEM BARK EXTRACTS OF Bombax buonopozense - Abdullahi, Samira A. (FUDMA JOURNAL OF SCIENCES, 2023)
Medicinal plants with antioxidant activities have been reported to be useful for the prevention of diseases. Bombax buonopozense is a wild tree found in Nigeria mainly in Nigeria. This study was aimed to determine in-vitro antioxidant activities of the methanolic extracts of leaf and stem bark of Bombax buonopozense (P. bauve). The phytochemical components of the methanolic leaf and stem bark extracts were qualitatively determined using standard methods. The antioxidant properties of the extracts specifically the DPPH free radical scavenging, reducing power and total antioxidant capacity were also carried by the method described by Dehshahri et al.,(2012) and preito et al.,(1999).  The result of the phytochemical screening revealed the presence of alkaloids, carbohydrates, cardiac glycosides, saponins, terpenoids, tannins and phenolics in the leaf extracts.The extract of the stem bark contains carbohydrates, cardiac glycosides, saponins, terpenoids, steroids, tannins and phenolics. At the lowest concentration of 0.2 mg/ml the leaf and stem bark extracts of the plant had DPPH free radical scavenging capacity of 88.9 and 88.9 % respectively. A significant difference (p < 0.05) was observed when the results of the samples was compared with that of ascorbic acid. The antioxidant potential of Bombax buonopozense  could be due to the phenols content, phenol donate electrons easily to electron-seeking free radicals, thus down-regulating their menace in living cells. Therefore, methanol extracts of the leaf and stem bark of Bombax buonopozense posses antioxidant activity and are rich in phenolics